PENGARUH BUDAYA ASING TERHADAP SIKAP NASIONALISME MAHASISWA PRODI PENDIDIKAN BAHASA JEPANG DAN PRODI PENDIDIKAN BAHASA INGGRIS UNIVERSITAS RIAU - Fitriana, Fitriana; Eddison, Ahmad; Supentri, Supentri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This research is motivated by Culture is a way of life that is developed and owned by a group of people and is passed down from generation to generation. Culture is made up of many complex elements, including religious and political systems, customs, language, tools, clothing, buildings and works of art. Culture is complex, abstract, and broad, many cultural aspects also determine communicative behavior as well as foreign cultures. The problem formula in this study is whether there is an influence of foreign culture on the nationalism attitude of Foreign Language students at Riau University. Students in foreign language education are active in organizing activities that carry both English and Japanese culture, especially in Japanese culture which is famous for its unique characteristics, from clothing to animated films that are popular with teenagers and adults alike. One of the activities of students majoring in Japanese is BUNKASAI, which includes many items for competitions (competitions) and events such as Cosplay which feature animated film clothes by Japanese artists. While the activities of English students are more focused on forms of expression of language mastery such as the English Olympiad, but if foreign cultures are consumed by many students, this is certainly the opposite of the role of the students themselves. Students are expected to have a high attitude of nationalism because students are a moral force, namely a group of people who have good morals, and students as social control, which means controlling social life, controlling social practices carried out by the community, especially the attitude of nationalism. The purpose of this research is based on the formulation of the problem. and according to the background that has been described, the purpose of this study is to determine whether there is an influence of foreign culture on the attitude of nationalism of foreign language students at the University of Riau. Influence is the power that exists or arises from something (person or thing) that helps shape the character of belief and a person's actions, culture or culture comes from the Sanskrit language, namely buddhayah, while foreign culture is a culture that comes from outside the area that is accepted and lived by a community who lives in its own area. Attitude According to Secord and Backman in (Azwar, 2002) Attitude is a certain order in terms of feelings (affection), thoughts (cognitive), and predisposition of one's actions (konasi) to an aspect of the surrounding environment, Nationalism is a nationalism that arises because of equality. fate and history, as well as the interest tolive together as an independent, united, and sovereign nation. Students are the names for people who are currently pursuing higher education in a tertiary institution consisting of high schools, academies, and most commonly a university. in research management using quantitative methods, The population in this study were all students of English education study program and Japanese language education study program at Faculty of Social and Political Sciences, Riau University, totaling 768 people, namely 490 English students and 278 Japanese language students, and 77 samples were taken. Data collection techniques using observation, interviews, and questionnaires. Based on the results of research conducted in the field, it can be concluded that the results of the regression model analysis in the F test show that the value of f-count> f-table is 25.475> 3.97, meaning that there is a significant overall effect between foreign cultures on the nationalism attitude of foreign language students at the University. Riau. In the t test, it was found that the value of t-count> t-table was 5.047> 1.671, which means that H_1 was accepted, meaning that there was a significant influence between foreign culture on the nationalism attitudes of foreign language students at the University of Riau.Key Words: Influence, Attitudes, Foreign Culture, Nationalism